Magnetic Evidence for an Extended Hydrogen Exosphere at Mercury. Issue 11 (15th November 2022) - Schmid, D.; Lammer, H.; Plaschke, F.; Vorburger, A.; Erkaev, N. V.; Wurz, P.; Narita, Y.; Volwerk, M.; Baumjohann, W.; Anderson, B. J.
Abstract: Remote observations by the Mariner 10 and MErcury Surface, Space ENvironment, GEophysics, and Ranging (MESSENGER) spacecraft have shown the existence of hydrogen in the exosphere of Mercury. However, to date the hydrogen number densities could only be estimated indirectly from exospheric models, based on the remotely observed Lyman‐α radiances for atomic H, and the detection threshold of the Mariner 10 occultation experiment for molecular H2 . Here, we show the first on‐site determined altitude‐density profile of atomic H, derived from in situ magnetic field observations by MESSENGER. The results reveal an extended H exosphere with densities that are ∼1–2 orders of magnitude larger than previously predicted. Using an exospheric model that reproduces the H altitude‐density profile allows us to constrain the so far unknown H2 density at the surface, which is ∼2–3 orders of magnitude smaller than previously assumed. These findings demonstrate the importance of (a) in situ measurements supporting remote observations of Mercury's exosphere that will be realized in the near future by the BepiColombo mission and (b) that dissociation processes play a crucial role in Mercury's exosphere. Plain Language Summary: Mercury has an exosphere that contains a variety of species. So far, only two spacecraft have probed the space environment around Mercury: Mariner 10 in 1974–1975 and MErcury Surface, Space ENvironment, GEophysics, and Ranging (MESSENGER) four decades later. Optical observations by Mariner 10 and MESSENGER showed that Mercury has a thin collisionless atmosphere (exosphere) which is abundant in hydrogen. To date the hydrogen number density at Mercury could only be estimated from exospheric models that use the optical observations as constrains, since no in situ measurements of hydrogen are available to determine its exact number density. For the first time, we derive an altitude‐density profile of Mercury's H exosphere from in situ magnetic field measurements by MESSENGER. From the observations of so‐called pick‐up ion cyclotron waves in the magnetic field data, it is possible to derive the local H number density, necessary to excite these waves. The results reveal an extended atomic H exosphere with densities decreasing from ∼100 to 10 cm −3 between 2, 400 and 15, 000 km above the surface. The unexpected large H densities can only be explained by dissociation processes of H2 molecules. Here, we introduce an exospheric model that includes such dissociation processes, which allows us for the first time to constrain the H2 number density. The results suggests that atomic H has additional sinks near the surface, most likely through chemical reactions with OH and O, and that the photochemistry of H2 O in general play an important role for Mercury's exospheric composition. Key Points: First on‐site determined hydrogen number density in Mercury's exosphere Demonstration that dissociation processes play an important role in Mercury's exosphere Based on the results, we can constrain the so far unknown and overestimated molecular surface number density of hydrogen